Development of a PjBL-Based Digital Flipbook Module on Chemical Bonding for Grace XI Students - Simbolon, Nasio Ruth Lusianna; Panggabean, Freddy Tua Musa (Universitas Negeri Medan, 2025)
Enhancing student engagement and conceptual understanding in chemistry requires innovative and interactive learning materials. This study aims to develop and evaluate a flipbook module based on Project-Based Learning (PjBL) for chemical bonding content. The research adopted the 4D development model—Define, Design, Develop, and Disseminate—focusing on content validity, student responses, and effectiveness in improving learning outcomes. Expert evaluations confirmed the module’s high validity, and student feedback indicated strong approval in terms of content, presentation, and language. The module also demonstrated moderate effectiveness in enhancing students' conceptual understanding, as shown by learning gains. These findings suggest that the PjBL-based flipbook module is feasible, pedagogically appropriate, and positively received, making it a valuable resource for supporting active and student-centered chemistry learning in high school settings.